Optimization of carbohydrate production by Chlorella minutissima under laboratory conditions - Singh, Surendra; sahu, Jyoti (International Journal of Scientific Research in Biological Sciences, 2020)
The global change in climate, the rising price of oil and the rapid depletion of fossil fuel reserves forced governments, scientists and researchers to invest in alternative energy sources, including wind and solar energy and biofuels. Microalgae are considered as the most promising renewable feedstock for biofuel production and biore-fineries, due to their advantages of fast growth, efficient carbon dioxide fixation, not competing for arable lands and potable water, and potentially accumulating high amounts of lipids and carbohydrates. Chlorella minutissima, microalgae, is a promising source of biomolecules, especially carbohydrates, for commercial exploitation. The present study is an attempt to optimize the culture conditions to enhance the intra- and extracellular carbohydrates in C. minutissima. The optimization experiment used the variations in photoperiod, turbulence, pH conditions as well as different media compositions. The results showed that a photoperiod of 12 h to 8 h of shaking and pH of 8.0 are best suited for optimal carbohydrate concentration, which can be increased from 28.2 % for intracellular and 24.3 % for extracellular carbohydrate on dry basis up to 45.6% and 40.3% for intra- and extracellular carbohydrate % respectively, showing 150% yield under optimized conditions. Among different media used, bold Basel media proved to be the best among others.